Analisis Sistematis Kesalahan Berbahasa Indonesia Pada Generasi Muda - Safira Afifah; Usiono Usiono (CV. ALIM'SPUBLISHING, 2025)
This study analyzes Indonesian language errors that are common among the younger generation, focusing on the influence of social media as one of the main causes. Data was collected from conversations on the WhatsApp platform and analyzed using a qualitative descriptive method. The results show that language errors that are often found include the use of non-standard abbreviations, spelling errors, punctuation, and capital letters. The main factors causing these errors are the habit of informal communication on social media and the lack of effective Indonesian language education. This research recommends updating Indonesian language learning methods that are relevant to the digital era as well as awareness campaigns for good language use through social media.